Penggunaan AREL pada Penyampaian Argumen di Klub Debat Bahasa Inggris STKIP PGRI Ponorogo - Rohmatika, Arina; Syamsuddin, Syamsuddin (Dinamika Ilmu: Jurnal Pendidikan, 2014)
The English debat organization is one of the most popular students’ activity units at STKIP PGRI Ponorogo. Many students of English department join this club. The skill of debate of the students in the English club is not improved yet. The objective of this study was to give an appropriate way of giving argument of a debate by using AREL. AREL is Argument, Reasoning, Evidance and Link Back. This is a classroom action research. The approach of this study is qualitative and quantitative. The qualitative data were gained by using questionnaire and observation. The quantitative data were gained from the result of the students’ speaking test both pre-test, post-test I, and post-test II. The subject of the study was the members of the English debate club of STKIP PGRI Ponorogo consisting of 19 students. The data collection technique used in this study was observation. The observation, then, also was enriched by recording and taking-note techniques. Data, then, was analyzed quantitatively and qualitatively. In pre-test, many students still made many mistakes in presenting the argument. Based on the pre-test data, the pre-treatment was done. In post-test I, some students made an improvement in presenting a good enough organization of an argument, but it was not good yet. In post-test II of the next treatment, it shows a better result